PENERAPAN PSAK NO. 45 GUNA MENINGKATKAN LAPORAN KEUANGAN YANG BERKUALITAS PADA MASJID HUSNUL KHOTIMAH KOTA KEDIRI (Fakultas Ekonomi Universitas Islam Kadiri (UNISKA) Kediri, 2024)
Abstract This research examines the implementation of PSAK No. 45 in the financial statements of Masjid Husnul Khotimah as a non-profit organization. PSAK No. 45 serves as a guideline for accounting for financial instruments and derivative contracts with the aim of enhancing the quality of financial reporting. The study encompasses an analysis of the mosque's accounting system, recording methods, transaction records, and financial transaction processes. Masjid Husnul Khotimah employs cash accounting and manual recording along with Microsoft Excel software. Cash receipts are sourced from regular donors, occasional contributors, and ad-hoc donations, while cash disbursements align with the established budget. The research identifies potential improvements in preparing financial statements in accordance with PSAK No. 45 to enhance transparency and financial accountability of the mosque to its congregation and other stakeholders. Due to the absence of proper accounting records, the researcher conducted accounting entries in accordance with PSAK No. 45. Keywords: Non-profit Organization, Financial Report of Mosque, PSAK No.45, Cash Accounting, Journal Abstrak Penelitian ini mengkaji tentang penerapan PSAK No. 45 dalam laporan keuangan Masjid Husnul Khotimah sebagai organisasi nirlaba. PSAK No. 45 berfungsi sebagai pedoman akuntansi untuk instrumen keuangan dan kontrak derivatif dengan tujuan untuk meningkatkan kualitas pelaporan keuangan. Kajian tersebut meliputi analisis sistem akuntansi masjid, metode pencatatan, pencatatan transaksi, dan proses transaksi keuangan. Masjid Husnul Khotimah menggunakan akuntansi kas dan pencatatan manual serta perangkat lunak Microsoft Excel. Penerimaan kas bersumber dari donatur tetap, donatur sesekali, dan donasi ad-hoc, sedangkan pengeluaran kas disesuaikan dengan anggaran yang telah ditetapkan. Penelitian ini mengidentifikasi potensi perbaikan dalam penyusunan laporan keuangan sesuai dengan PSAK No. 45 untuk meningkatkan transparansi dan akuntabilitas keuangan masjid kepada jamaahnya dan pemangku kepentingan lainnya. Karena tidak adanya pencatatan akuntansi yang baik, maka peneliti melakukan pencatatan akuntansi sesuai dengan PSAK No.45. Kata Kunci : Organisasi Nirlaba, Laporan Keuangan Masjid, PSAK No.45, Akuntansi Kas, Jurnal